2021
DOI: 10.2147/jmdh.s314004
|View full text |Cite
|
Sign up to set email alerts
|

Survival Time and Associated Factors Among Adults Living with HIV After Initiation of HAART in South Gondar, Northwest Ethiopia: A Retrospective Cohort

Abstract: Background Antiretroviral therapy consistently improves the survival of people living with HIV and contributes to preventing the development of new infections. Studies of antiretroviral therapy programs in Africa have shown a high mortality rate during the first 6 months after initiation of HAART in rural health facilities. This study looks at survival time and associated factors among adults with HIV in south Gondar, Northwest Ethiopia. Methods A 5-year retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
4
7
1
Order By: Relevance
“…This was not consistent with other study conducted in Ethiopia during the year 2006-2010 that reported 7% mortality at 36 months of follow-up [34]. Other study conducted in Gonder, Ethiopia, in the year 2010-2014 reported mortality at 60 months of follow-up to be 13.67% [8] which is relatively similar to our second HAART cohort, initiating HAART during 2010-2013, that revealed a 10.03% mortality. Despite the study group were children, a study conducted in Gamo Gofa Zone, Ethiopia, conducted from 2009 to 2016 reported mortality in the 60 months of follow-up to be 26.1% which was not in line with our report that showed 4.34% mortality in the year 2014-2016 [16].…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…This was not consistent with other study conducted in Ethiopia during the year 2006-2010 that reported 7% mortality at 36 months of follow-up [34]. Other study conducted in Gonder, Ethiopia, in the year 2010-2014 reported mortality at 60 months of follow-up to be 13.67% [8] which is relatively similar to our second HAART cohort, initiating HAART during 2010-2013, that revealed a 10.03% mortality. Despite the study group were children, a study conducted in Gamo Gofa Zone, Ethiopia, conducted from 2009 to 2016 reported mortality in the 60 months of follow-up to be 26.1% which was not in line with our report that showed 4.34% mortality in the year 2014-2016 [16].…”
Section: Discussioncontrasting
confidence: 91%
“…Other study conducted in Ethiopia also revealed being bedridden as 17.4 times risk of death compared to ambulatory patients [ 34 ]. A study conducted in Gonder, Ethiopia, also revealed a 9.57 times risk of death among bedridden [ 8 ]. Our study was consistent with other previous studies and may highlight the importance of early HIV testing and treatment to ensure better survival of PLHIV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations